Enhancing nutritional support for Zimbabwe HIV-positive rural learners with albinism during El Niño-induced drought: School Development Committee role - Chidarikire, Munyaradzi; Mhlanga, Songile (EDUCATIO : Journal of Education, 2024)
This qualitative study examines the role of School Development Committees in enhancing nutritional support for HIV-positive rural learners with albinism during El Niño-induced droughts in Zimbabwe. Using a purposive sampling approach, 18 participants were selected to ensure diverse representation, including parents, NGO representatives, village heads, social workers, government officials, church leaders, and teachers. Learners were excluded from participation to uphold ethical standards protecting minors. Data collection involved a three-hour focus group discussion, fostering open dialogue in participants' preferred language. Thematic analysis revealed important insights into the need for targeted nutritional programs and the significance of multi-sectoral partnerships. Findings highlight the critical capacity of School Development Committees to mobilize community resources and promote collaboration, ultimately improving educational outcomes and well-being for HIV-positive learners with albinism. A key finding of the study is that School Development Committees are instrumental in mobilizing local resources and facilitating collaboration among various stakeholders, which is vital for creating supportive educational environments for HIV-positive learners with albinism. It is recommended that educational authorities enhance the effectiveness of School Development Committees by providing targeted training and resources, enabling them to better address the nutritional and educational needs of vulnerable learners during drought conditions.